Analisis Aspek Sosial Budaya Dalam Cerpen Ibuku, Perempuan Dari Pulau Rote Karya Fanny J. Poyk - Aditya Budi Nugraha (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to describe the social and cultural aspects in the short story Ibuku, Perempuan dari Pulau Rote by Fanny J. Poyk. The research method used is descriptive qualitative. The object of study in this short story is social aspects. The data needed in this research are paragraphs in the short story “Ibuku, Perempuan dari Pulau Rote” by Fanny J. Poyk. The social aspects in “Ibuku, Perempuan dari Pulau Rote” by Fanny J. Poyk are analyzed using literary sociology techniques. The research results of the analysis that has been carried out, there are five social aspects contained in the short story “Ibuku, Perempuan dari Pulau Rote” by Fanny J. Poyk, namely (1) Social organization in the form of an empire. The form of social organization is in the form of an empire (kingdom) (2) Religion, adhering to the monotheism system (3) The system of knowledge and magic which is still very classical and has not been touched by modernization (4) The system of livelihood, namely trade (5) Arts, namely performing arts and musical instruments. Art can be in the form of making woven fabrics in this case.